The performance of Panggung Bangsawan in Riau Lingga; A reconstruction of a theatrical process - Arybowo, Sutamat (UI Scholars Hub, 2010)
Panggung Bangsawan is a popular folk theatre in Riau Lingga. The ups and downs in its performance are atributed to changes in social, political, and cultural conditions. This article is a reconstruction of a near extinct Panggung Bangsawan group in the Teluk village in the islands of Riau Lingga. First, I have attempted to describe the staging process; second, to endeavour to understand the phenomenon of change which occurs when a folk tale is transformed from written work into a performance; and third, to expose the transformation of a script (text) divided into scenes into a performance. This is an attempt to explain the relation between the audience's response to a text when it is staged. This article is expected to give a more profound understanding on how the society supporting Panggung Bangsawan remember their past and their ideal views while comprehending how the shift in life values emerges in a staged folk tale.